A escola como espaço de formação continuada de professores: o caso da Escola Cidade de Emaús, Belém/Pa - BARROS, Maricilda Nazaré Raposo de (Universidade Federal do Pará, 2011)
Made available in DSpace on 2011-03-23T21:19:24Z (GMT). No. of bitstreams: 0 === Item created via OAI harvest from source: http://www.bdtd.ufpa.br/tde_oai/oai2.php on 2011-03-23T21:19:24Z (GMT). Item's OAI Record identifier: oai:bdtd.ufpa.br:176 === In this research, I have perspective, contribute for the discussion of the continued formation of teachers centered in school, having as locus of research the School City of Emaús, in Belém/Pa. With the purpose to knowing the process of continued formation taken place in this school it analyzes primary documents of the Institution, that deal with its philosophy, of the social statute of the maintainer entity, of the politician-pedagogical project, among others and interviews with 06 diligent teachers of this experience who had started to participate of the school space in elapsing of the considered period, in which if it includes author and its proper memories. For the reconstitution of the process I used the narrative research, looking for evidence the implanted partner-pedagogical experience since the decade of 1980 that it is configured since than, as one other/new proposal educational up to 2003. Considering for the study of the process the following axles of analysis: the formative organization of space and pertaining to school time and actions in the school, considering there the collective work, the production of didactic materials, the politic social involvement and the activities done in the district. I discuss the advances and limitation of the continued formation of teachers centering in the school and I search to point out ways to the construction of the necessary teacher to proposal of a politician-pedagogical project to this educative space, it still looks, to join technique ability to the commitment politician. This formation must assure the permanent confirmation and evaluation of the philosophy assumed by the school, as well as all theoretician-scientific recital of the work developed there, materialize the actions from the proper experience of a collective work. This formation therefore, acquires an essential character of the pertaining to school community. I also think, that from an interior politicianpedagogical project, in fact, for the diverse segments of a pertaining to school institution there are greater conditions, so that if it constructs a central axle to the continued formation of teachers, who are just integrant part of people who must concur for the same purpose. I believe the school that possess a politician-pedagogical project, compels it to the necessity of forming responsible human resources for its development. === Neste trabalho tenho como perspectiva, contribuir para a discussão da formação continuada de professores centrada na escola, tendo como lócus de pesquisa a Escola Cidade de Emaús, em Belém/Pa. Com o objetivo de conhecer o processo de formação continuada realizado nesta escola analiso documentos primários da Instituição, que tratam de sua filosofia, do estatuto social da entidade mantenedora, do projeto político-pedagógico, dentre outros e entrevistas com 06 professoras trabalhadoras dessa experiência que passaram a participar do espaço escolar no decorrer do período considerado, nas quais se inclui autora e suas próprias memórias. Para a reconstituição do processo utilizei a pesquisa narrativa, buscando evidenciar a experiência sócio-pedagógica implantada desde a década de 1980 que se configura, desde então, como uma outra/nova proposta educacional até 2003. Foi considerado para o estudo do processo os seguintes eixos de análise: a organização de espaços e tempos escolares e as ações formativas na escola, considerado aí o trabalho coletivo, a produção de materiais didáticos, o envolvimento político-social e as atividades realizadas no/com o bairro. Discuto os avanços e limitações da formação continuada de professores centrada na escola e busco apontar caminhos para a construção do professor necessário à proposta de um projeto políticopedagógico pensado para esse espaço educativo, que procura, ainda, aliar competência técnica ao compromisso político. Essa formação deve assegurar a permanente reafirmação e avaliação da filosofia assumida pela escola, bem como toda fundamentação teórico-científica do trabalho ali desenvolvido, concretizando as ações a partir da própria vivência de um trabalho coletivo. Essa formação, portanto, adquire um caráter imprescindível dentro da comunidade escolar. Penso, inclusive, que a partir de um projeto político-pedagógico internalizado, de fato, pelos diversos segmentos de uma instituição escolar haja maior condição para que se construa um eixo central para a formação continuada de professores, que são apenas parte integrante de um corpo de pessoas que devem concorrer para a mesma finalidade. Acredito que a escola possuidora de um projeto político-pedagógico, obriga-se à necessidade de formação dos recursos humanos responsáveis por seu desenvolvimento.